RISK FACTORS FOR CARDIOVASCULAR EVENTS IN RURAL NIGERIA: A CROSS SECTIONAL SURVEY AND A REVIEW OF THE CURRENT LITERATURE - Anthonia A. Ikpeme*, Nchiewe E. Ani, Edoise M. Isiwele,Andrew E. Ekpenyong,Emmanuel E. Ekanem (Innovative Journal of Medical and Health Sciences, 2019)
Introduction: Over 80% of cardiovascular deaths take place in low and middle income countries. These cardiovascular deaths are caused by modifiable risk factors. Evidence is emerging that some of these factors maybe even more prevalent in rural areas which are generally underserved. Aim: The aim of this study was to record risk factors for cardiovascular disease in rural communities in south southern Nigeria and review some related literature. Methods: A cross sectional study during clinical outreach activities that took place in 2016 to 2018 in several rural and few urban communities in Cross River State, Nigeria. Participating individuals gave full consent and ethical clearance obtained. Socio-demographic data, Anthropometric data and Blood sugar measurements were obtained. Data extracted was transferred into EXCEL thereafter analysis was done using SPSS version 21. p values less than 0.05 were deemed statistically significant. Tests of significance included Anova, chi square and student t- tests. Results: Total population investigated over the 3 year period was 504. (2016-33.1%), (2017 -37.9%), (2018 – 28%) with a Female: Male distribution of 1:1. Most participants tended to be overweight across the years 59.7%, 59.1%, 73.7%, 2016, 2017, and 2018 respectively. The prevalence of Hypertension was 10.71%. No significant gender difference in the prevalence of Hypertension (6.94% males to 3.77% females, p=0.097). The prevalence of Diabetes Mellitus was 10.67%. There was no significant gender prevalence (6.67% males to 4.00% females, p =0.431) Conclusion: Cardiovascular disease remains relatively uncommon in Sub-Saharan Africa, despite an increasing prevalence of risk factors, but it’s incidence is rising. Steps should be taken in Sub-Saharan Africa to prevent an epidemic. This involves detailed and regular screening for cardiovascular risk factors in rural communities. Key words: RISK FACTORS, Cardio vascular disease, South South Nigeria.